Profiling Learning Style of Excellent Graduate Students - Rihza Galih Faturrochman; Lies Amin Lestari; Widyastuti Widyastuti (Electronic Journal of Education, Social Economics and Technology, 2025)
This study investigated the learning styles of high-achieving postgraduate students, a topic with conflicting findings in existing literature on the relationship between learning styles and academic achievement. Employing a qualitative case study design, the research sought to gain a deeper understanding of this phenomenon by utilizing two distinct instruments. First, the VARK questionnaire was administered to provide a quantitative measure of each participant's sensory preferences. Subsequently, semi-structured interviews were conducted to explore their actual learning strategies and experiences in the specific context of a master's degree program. The findings revealed a compelling divergence: while the questionnaire identified distinct sensory preferences for each participant, their academic practices were not rigidly aligned with these results. Instead, their success appeared to be a product of a strategic and adaptive approach, with a willingness to employ diverse methods like reading and practicing to meet the rigorous demands of their curriculum. This suggests that academic achievement in higher education is less about a fixed learning style and more about a student's capacity for self-regulated, metacognitive adaptation. These results offer a nuanced perspective on the learning style debate, emphasizing the importance of cultivating flexible learning strategies rather than simply diagnosing a single preference.